2022
DOI: 10.3390/vaccines10030443
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Time of Day of Vaccination with BNT162b2 on the Adverse Drug Reactions and Efficacy of Humoral Response against SARS-CoV-2 in an Observational Study of Young Adults

Abstract: An increasing body of evidence from both academic and clinical studies shows that time-of-day exposure to antigens might significantly alter and modulate the development of adaptive immune responses. Considering the immense impact of the COVID-19 pandemic on global health and the diminished efficacy of vaccination in selected populations, such as older and immunocompromised patients, it is critical to search for the most optimal conditions for mounting immune responses against SARS-CoV-2. Hence, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…[ 99 ] However, another recent study demonstrated no statistical difference in antibody response and chronotypes to the time‐of‐day administration of the SARS‐CoV‐2 vaccination. [ 100 ] Currently, we have limited evidence to support the timing of the SARS‐CoV‐2 vaccination and its related efficacy. More studies are needed to ascertain whether dosing the COVID‐19 vaccine at a specific time of day mediates a higher degree of protective immune response in the general population and among NSW.…”
Section: Circadian Clock Disruption In Night Shift Workmentioning
confidence: 99%
“…[ 99 ] However, another recent study demonstrated no statistical difference in antibody response and chronotypes to the time‐of‐day administration of the SARS‐CoV‐2 vaccination. [ 100 ] Currently, we have limited evidence to support the timing of the SARS‐CoV‐2 vaccination and its related efficacy. More studies are needed to ascertain whether dosing the COVID‐19 vaccine at a specific time of day mediates a higher degree of protective immune response in the general population and among NSW.…”
Section: Circadian Clock Disruption In Night Shift Workmentioning
confidence: 99%
“…Although previous studies with inactivated vaccines have suggested a potential relationship between the time of day of vaccination and antibody acquisition ( 25 ), the results of observational studies using the mRNA vaccine have been inconsistent. One study reported that afternoon vaccination resulted in higher antibody titers ( 34 ), while another study suggested that the timing of vaccination had no effect on antibody titers ( 35 ). The cause of this disparity is not clear, but the nature of long-acting feature of the mRNA vaccine may have mitigated the effect of the time of day of vaccination ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several strengths. Biological rhythms in vaccination are an understudied topic, with only 12 published studies in patients, including 6 focused on COVID-19 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These prior studies differ on whether optimal vaccination times exist, what times of day produce optimal vaccine responses, and whether the effect is specific to certain patient subsets.…”
Section: L N I C a L M E D I C I N Ementioning
confidence: 99%
“…Some theorize that the circadian rhythms in humans should translate, directly or indirectly, into preferable times of day to vaccinate patients (1,2,(19)(20)(21)(22)(23). However, clinical studies are equivocal on whether rhythms exist in vaccine responses, including those against SARS-CoV-2, the cause of COVID-19 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). While important, prior studies reported surrogate markers of immunogenicity like antibody titers rather than clinical outcomes and had limited sample sizes.…”
Section: Introductionmentioning
confidence: 99%